Combined evaluation of corporate ecological and environmental responsibility: Evidence for forest preservation from Chinese forestry companies - Long, Fengjiao; Strielkowski, Wadim; Liu, Xiaomin; Uppal, Raminder Singh; Chen, Qin (Frontiers in Ecology and Evolution, 2022)
The ecological benefit of forest has an important influence on the sustainable development of society, thus, forest management has become a critical strategic action. Forest preservation is an inclusive process which depends on collaboration among a wide range of stakeholders. Forestry companies, who own and manage forest resources, are responsible for forest preservation and ecological construction, which is called corporate ecological environmental responsibility (CEER). Most existing analyses, however, were limited to corporate environmental responsibility (CER) and ignored the ecological responsibility of forestry enterprises. Therefore, in order to better play the role of forestry companies in forest preservation, it is urgent to define the content and the measurement of CEER. This paper established a CEER index system based on the characteristics of forestry enterprises. Furthermore, evaluated the CEER level of forestry enterprises using the combined evaluation method based on the GINI criterion, which is more effective and reasonable. It is found that forestry ecological environmental responsibility emphasizes ecological improvement and has shifted from traditional environmental protection to ecological construction. Qingshan Paper, Sun Paper, and Yong’an Forestry perform the best in CEER among all forestry companies. In addition, the results showed a low level but an obvious upward trend in forestry CEER and a noticeable heterogeneity in the performance of CEER in different forestry industries. Our findings can be useful for further promoting the ecological benefits of forest companies and developing relevant policies.